2013
DOI: 10.1111/gove.12045
|View full text |Cite
|
Sign up to set email alerts
|

Microblogs and the Adaptation of the Chinese Party‐State's Governance Strategy

Abstract: The Chinese party-state is currently adapting its governance strategy. The recent debate in China on the role of microblogs in the governance process, as documented in the reports issued by Chinese research institutes and advisory bodies, illustrates the efforts being undertaken by China's political elites to integrate microblogs into their new public management strategy. Mass protests and large-scale online criticism-voiced via microblogsdirectly threaten the regime's survival. As a consequence, legitimacy is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 29 publications
(27 reference statements)
0
42
0
Order By: Relevance
“…Such a mix of instruments can circumvent the "dilemma of the dictator" (Wintrobe, 1998; see also Göbel, 2013, p. 388), which means governing in an environment of low information quality and marginal citizen trust because of the repressive nature of autocratic rule. Deliberative instruments include a partial media liberalization (Egorov, Guriev, & Sonin, 2009;Lorentzen, 2014;Stier, 2015), government usage of microblogs (Noesselt, 2014) and allowing some government criticism online (King, Pan, & Roberts, 2013). However, these instruments inhere a potential for collective action, as they can also be used by the political opposition.…”
Section: Autocracy and E-governmentmentioning
confidence: 99%
“…Such a mix of instruments can circumvent the "dilemma of the dictator" (Wintrobe, 1998; see also Göbel, 2013, p. 388), which means governing in an environment of low information quality and marginal citizen trust because of the repressive nature of autocratic rule. Deliberative instruments include a partial media liberalization (Egorov, Guriev, & Sonin, 2009;Lorentzen, 2014;Stier, 2015), government usage of microblogs (Noesselt, 2014) and allowing some government criticism online (King, Pan, & Roberts, 2013). However, these instruments inhere a potential for collective action, as they can also be used by the political opposition.…”
Section: Autocracy and E-governmentmentioning
confidence: 99%
“…Governments also embrace the bandwagon to engage the public and rebuild public legitimacy (Noesselt 2014 ), making 2010 immediately becomes the milestone of government microblogging development (Zheng 2013 ;Schlaeger and Jiang 2014 ).…”
Section: The Use Of Microblogging In Chinese Public Sectorsmentioning
confidence: 99%
“…22 After surveying the Chinese government's uses of and attitudes toward social media, she concluded that the CCP has come to view social media, including microblogging, as a route to popular political legitimacy. 22 After surveying the Chinese government's uses of and attitudes toward social media, she concluded that the CCP has come to view social media, including microblogging, as a route to popular political legitimacy.…”
Section: Government Microblogs and Contentionmentioning
confidence: 99%